RESIDENTIAL BUILDING’S DEFORMATION ON PILE FOUNDATION - Vynnykov, Yuriy; Manzhalii, Sergiy (Academic journal Industrial Machine Building Civil Engineering, 2019)
A considerably distinctive deformed five-storeyed three-section brick residential house erected over 40 years ago on drivenprismatic piles combined by a strip grid foundation by a standardized project is under investigation. The geotechnical monitoring results of the building's technical condition are presented. Methods and results of the instrumental control analysis ofthe piles' actual length and visual evaluation of their integrity are presented. The causes of the foundations base's excess deformation were determined: the inability of the piles' tips to reach the designed mark; the piles' destruction during their immersion in dense sands; rupture of the primary thermal network, which led to "negative friction" effect on the piles' lateralsurface, etc.
Keywords: soil base; sand; soft soil; driven prismatic pile; grid foundation; settlement; crack; tension bar; engineering status of the building; geotechnical monitoring